Penanaman Nilai Pancasila dan Semangat Kebangsaan Melalui Pendidikan Kewarganegaraan - Fahrurrozhi, Alfian; Oktaviani, Dwi; Lestari, Dwi Indah (Universitas Cokroaminoto Yogyakarta, 2021)
Instilling the values of Pancasila and the spirit of nationalism through civic education. Historically, education has played an important role in developing the value of nationalism in Indonesian society for everyone. Currently, education, especially civic education, has an efficient and important role and fully contributes to preserving, and enhancing the ideological values of the state and nationalism in the nation's next generation. multiculturalism education and educational conflict. Citizenship education must be understood as fully as possible in order to increase the efficiency of the next generation. This means teaching students to solve social problems critically and analytically and to apply the spirit of ideology and values of nationalism. Therefore, civic education is taught not only as an intermediary, but also as a reflective inquiry. To that end, Indonesia is starting to strengthen civic education, integrating direct and indirect approaches to values education and expecting students to internalize national ideology and nationalist values as beliefs. Furthermore, several principles of a strong teaching and learning process must also be communicated to Indonesian school residents.